2007
DOI: 10.1186/1471-2164-8-175
|View full text |Cite
|
Sign up to set email alerts
|

An early response regulatory cluster induced by low temperature and hydrogen peroxide in seedlings of chilling-tolerant japonica rice

Abstract: Background: Plants respond to low temperature through an intricately coordinated transcriptional network. The CBF/DREB-regulated network of genes has been shown to play a prominent role in freeze-tolerance of Arabidopsis through the process of cold acclimation (CA). Recent evidence also showed that the CBF/DREB regulon is not unique to CA but evolutionarily conserved between chilling-insensitive (temperate) and chilling-sensitive (warm-season) plants. In this study, the wide contrast in chilling sensitivity be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(112 citation statements)
references
References 62 publications
10
101
0
1
Order By: Relevance
“…The stability of the plasma membrane under cold conditions in JERF3-expressing tobacco indicates that regulation of JERF3 by oxidative stress might occur via a similar ROS-regulatory pathway. The involvement of JERF3 in ROS is also supported by the fact that JERF3 interacts with the ROS-responsive as-1 element in a transient assay, consistent with the report that a bZIP-type protein, which interacts with as1/ocs-like elements in the promoters of target genes, might be a component of the ROS-mediated pathway (Cheng et al, 2007). However, the predicted regulatory relationship between ROS-bZIP1 and the as1/ocs element-containing genes awaits further confirmation.…”
Section: Discussionsupporting
confidence: 87%
“…The stability of the plasma membrane under cold conditions in JERF3-expressing tobacco indicates that regulation of JERF3 by oxidative stress might occur via a similar ROS-regulatory pathway. The involvement of JERF3 in ROS is also supported by the fact that JERF3 interacts with the ROS-responsive as-1 element in a transient assay, consistent with the report that a bZIP-type protein, which interacts with as1/ocs-like elements in the promoters of target genes, might be a component of the ROS-mediated pathway (Cheng et al, 2007). However, the predicted regulatory relationship between ROS-bZIP1 and the as1/ocs element-containing genes awaits further confirmation.…”
Section: Discussionsupporting
confidence: 87%
“…6). It is known that a variety of abiotic stresses, such as heavy metals, drought, salinity, extreme temperatures, high irradiance, and UV light, cause oxidative damage to plants either directly or indirectly through the formation of ROS [17][18][19][20][21][22]. Our present work showed that MWCNTs result in a significant induction of intracellular ROS formation in plant cells after treatment with 20 mg/L S-MWCNTs (Fig.…”
Section: Figure 4 Heresupporting
confidence: 61%
“…Thus, ROS production initiates an early adaptational signal cascade to unfavorable ionic root environments. Similarly, the early response regulatory network triggered by oxidative signals is of great importance for the adaptation of rice to cold stress (Cheng et al, 2007). Moreover, genes responding to oxidative stress are activated earlier than those mediated by ABA (Yun et al, 2010).…”
Section: Introductionmentioning
confidence: 99%